Domain-speciﬁc and general-purpose acceleration in reconﬁgurable and Vector processor platforms - Alves, Fredy Augusto Maciel (2019)
Many heterogeneous CPU-FPGA platforms have emerged in the past few years ranging from large systems to single chip nodes. In this work we present three diﬀerent papers implemented on this type of heterogeneous platform. The ﬁrst one explains the implemen- tation of a collision detector accelerator, the second one compares this implementation to a boolean gene regulatory network accelerator and other applications, it derives lessons learned about what to take into consideration before implementing for heterogeneous systems. The third paper compares two diﬀerent vector processor ISAs, vector register (VR) and vector memory (VM). It shows the advantages of using VM over VR. The focus of the ﬁrst and second work is on the acceleration of speciﬁc applications for a speciﬁc platform, the focus of the third one is to compare two diﬀerent vector ISAs on the same platform for both. Keywords: FPGA. Vector Processor. Hardware Accelerator.